2012
DOI: 10.1007/s12061-011-9074-8
|View full text |Cite
|
Sign up to set email alerts
|

The Varying Impact of Geographic Distance as a Predictor of Dissatisfaction Over Facility Access

Abstract: This research uses a Geographically Weighted Regression (GWR) analysis to compare perceptions of public service accessibility as captured by an attitudes survey against measures of geographical distance to those services. The 2008 Place Survey in Leicestershire, UK, captured data on respondent dissatisfaction about their access to different services and facilities. In this analysis, survey responses about access to Post Offices and libraries were summarised over census Output Areas. Road distances to the neare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 33 publications
0
13
0
3
Order By: Relevance
“…Existe una amplia literatura internacional que aborda el tema de la accesibilidad a diferentes espacios urbanos como elemento primordial del bienestar de los individuos, y como una condición de justicia e inclusión social, participación y compromiso público (Stanley, 2012;Dai, 2011;Comber et al, 2012;Lotfi y Koohsari, 2009). En el Reino Unido la inclusión de la accesibilidad es primordial en la proposición de reformas estructurales fundamentales entre Estado y sociedad (Cabinet Office, 2010).…”
Section: Condicionantes Teóricas Del Uso De Parques Recreativosunclassified
See 1 more Smart Citation
“…Existe una amplia literatura internacional que aborda el tema de la accesibilidad a diferentes espacios urbanos como elemento primordial del bienestar de los individuos, y como una condición de justicia e inclusión social, participación y compromiso público (Stanley, 2012;Dai, 2011;Comber et al, 2012;Lotfi y Koohsari, 2009). En el Reino Unido la inclusión de la accesibilidad es primordial en la proposición de reformas estructurales fundamentales entre Estado y sociedad (Cabinet Office, 2010).…”
Section: Condicionantes Teóricas Del Uso De Parques Recreativosunclassified
“…Ésta puede basarse en las propiedades de los lugares en cuestión, como la estética y las comodidades que ofrecen (Witten et al, 2008;Matsuoka, 2008), así como también en otras características, como la inseguridad, la presencia de determinados grupos sociales o demográficos, percepción que muchas veces es negativa (Chiesura, 2004;Lotfi y Koohsari, 2009;Pain et al, 2006). Otros autores (Comber et al, 2012) incluyen en el tema de la accesibilidad las condiciones socioeconómicas de los usuarios, es decir, la capacidad económica para costear el trayecto y uso, así como la experiencia previa que tengan de dicho espacio. Por ende, se entiende como falta de accesibilidad el recorrido de trayectos largos, las limitantes percibidas tales como inseguridad, nula estética, falta de comodidades y servicios, así como la incapacidad económica para pagar el bien en cuestión.…”
Section: Condicionantes Teóricas Del Uso De Parques Recreativosunclassified
“…Libraries are public service centres in the UK as in elsewhere. The importance of libraries with its development from the traditional educational and cultural perspectives in the past, to where they have become modern information centres has been acknowledged [1]. Libraries are very useful and beneficial to the society, particularly the neighbourhood [2].…”
Section: Introductionmentioning
confidence: 99%
“…Many of these agencies are therefore faced with the difficulty of determining which facilities to close and at the same time minimising the negative effects of such closures. Comber and others [1] observed that libraries are usually included among facilities for planned closures whenever such discussions arise. Such closures, if not carefully optimised, could lead to processes of socio-spatial marginalization and exclusion [1].…”
Section: Introductionmentioning
confidence: 99%
“…To this end, geographically weighted regression (GWR) is a novel way to examine the spatial heterogeneity in rates of timely mammography by race/ethnicity. Past studies have shown that GWR is an effective way to not only document local variations in health outcomes, [35] but also service usage [36]. While multi-level modeling strategies, commonly used in urban health research [3740], can examine the interrelation between individual and neighborhood characteristics, they are limited in that they treat local effects as stationary and mutually independent across neighborhoods [41].…”
Section: Introductionmentioning
confidence: 99%